(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The purpose of this study is to find out Future of Learning that is improving technically and Providing Distance Learning. Computer assisted education makes available study material online with various Multimedia formats and Platforms that make easy access to study for students anywhere in world. Not only Students, Teachers as well using online Platforms to Teaching. In Pandemic Education is shifted to online Platform for some time, it helps Teachers and students communicating easily without any physical rooms. People also learn how to use computer and smartphones, which are mainly used for Computer assisted education. In spite of that doesn’t mean computer assisted education is going to replace class room study method.Butthere are few things that is adopted by teachers is Smart class concept that helps teachers to explain their view in more effective way, videos are also helping a lot changes in traditional education. In this Pandemic situation we have opted computer assisted education first time for so long that’s why teachers as well as students face some difficulties because, they are not used to this mode of education and improper training. For now,we have learnt how to use computer assisted education, also we are improving technologies like computer networks,E-learning platforms,cloud technology.